Analisis Kesiapan Guru Kelas 4 di SDN 3 Troso dalam Implementasi Kurikulum Merdeka - Prasetiyo, Ari; Zumrotun, Erna (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The Merdeka Learning Curriculum is a policy of the Ministry of Education, Culture, Research and Technology which aims to optimize the existing curriculum. The purpose of this study is to analyze the readiness of 4th grade teachers in SDN 3 Troso in implementing the Free Learning Curriculum. The research method is a case study involving two teachers and school principals in the elementary school implementing the Merdeka Learning Curriculum. This study was collected based on interviews, observations, and documentation. Then analyzed through data collection, data reduction, data presentation and conclusions. The results of this study indicate that the teacher's readiness in the application of the independent curriculum seen from the results of the interviews in accordance with the 6 indccariat shows that the teacher is still not ready in implementing an independent curriculum. Still lacking understanding regarding the structure of the independent curriculum and still needs training related to the preparation of the teaching module and learning assessment at Kurkulum Merdeka. The teachers still do not have a clear picture related to the application of the Merdeka Curriculum. The level of readiness shown can be a consideration for schools to immediately respond to problems. In addition, the concept of an independent curriculum needs to be understood by all elements of educational institutions, so that in its application it can run optimally, effectively, and efficiently and be able to achieve the goals of Kurikum Merdeka itself